2009
DOI: 10.1037/a0015861
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of children’s self-regulation and classroom quality to children’s adaptive behaviors in the kindergarten classroom.

Abstract: In this study, the authors examined the extent to which children's self-regulation upon kindergarten entrance and classroom quality in kindergarten contributed to children's adaptive classroom behavior. Children's self-regulation was assessed using a direct assessment upon entrance into kindergarten. Classroom quality was measured on the basis of multiple classroom observations during the kindergarten year. Children's adaptive classroom behavior in kindergarten was assessed through teacher report and classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
328
5
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(382 citation statements)
references
References 85 publications
20
328
5
7
Order By: Relevance
“…Conceptually, it has been suggested that contexts that provide better organizational support, where teachers use proactive approaches to monitor children's behavior, establish predictable routines in the classroom, and provide activities that are inherently interesting, are important for children's selfregulation (Downer et al, 2010, Hamre et al, 2014Rimm-Kaufman et al, 2009). …”
Section: Classroom-level Quality Processes and Children's Self-regulamentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, it has been suggested that contexts that provide better organizational support, where teachers use proactive approaches to monitor children's behavior, establish predictable routines in the classroom, and provide activities that are inherently interesting, are important for children's selfregulation (Downer et al, 2010, Hamre et al, 2014Rimm-Kaufman et al, 2009). …”
Section: Classroom-level Quality Processes and Children's Self-regulamentioning
confidence: 99%
“…Recent research has attempted to differentiate classroom quality into distinct dimensions, namely emotional, organizational, and instructional support, and to explore its differential effects on children's outcomes (Downer, Sabol, & Hamre, 2010;Hamre, Hatfield, Pianta, & Jamil, 2014;Rimm-Kaufman, Curby, Grimm, Nathanson, & Brock, 2009). Conceptually, it has been suggested that contexts that provide better organizational support, where teachers use proactive approaches to monitor children's behavior, establish predictable routines in the classroom, and provide activities that are inherently interesting, are important for children's selfregulation (Downer et al, 2010, Hamre et al, 2014Rimm-Kaufman et al, 2009).…”
Section: Classroom-level Quality Processes and Children's Self-regulamentioning
confidence: 99%
“…Indeed, research on children's difficult temperament points to negative associations with academic and social outcomes (e.g., Molfese et al, 2010;Stright, Gallagher, & Kelly, 2008). At the same time, there is growing support for the role of classroom quality in children's academic and social success Rimm-Kaufman, Curby, Grimm, Nathanson, & Brock, 2009). Thus, the present study examines how temperament and classroom quality work in combination by evaluating the moderating role first grade classroom quality has on the relations between children's difficult temperament (assessed in infancy) and their academic and social outcomes (reported in first grade).…”
mentioning
confidence: 99%
“…In order to regulate and optimize children's experiences in the classroom, given previous research showing associations between teacher-child interactions and child outcomes Hamre et al, 2007;Rimm-Kaufman et al, 2009), including in Portugal (Cadima et al, 2010, it may be important to focus directly on the classroom interactions. For example, Howes et al (2008) suggested that to better support children's learning, focusing on classroom processes could be more effective rather than simply specifying structural indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Findings have shown that high levels of emotional, organizational and instructional support are associated with academic achievement and social performance La Paro et al, 2004;Ponitz et al, 2009;Rimm-Kaufman et al, 2009), including in Portugal (Cadima, Leal, & Burchinal, 2010). Given these findings, descriptions of classroom quality and its predictors can provide important information to advance discussions on how to improve the learning experiences for children.…”
mentioning
confidence: 99%